Базові інтерпретаційні гіпотези концепту корупції - Гладкий, В. В. (Institute for Social Transformation, 2018)
У даній статті автор переслідує в якості мети дослідження основних підходів до розуміння терміну «корупція», на підставі чого формулює авторську дефініцію відповідного поняття. Вирішуючи поставлені завдання, що відповідають цілям дослідження, автор визначає, що закріплену в українському законодавстві дефініцію поняття «корупція» слід вважати невиправдано обмеженою. Зважаючи на це, підкреслюється необхідність приведення відповідної дефініції у відповідність з останніми науковими досягненнями в теорії корупційної та антикорупційної практики. В данной статье автор преследует в качестве цели исследование основных подходов к пониманию термина «коррупция», на основании чего формулирует авторскую дефиницию соответствующего понятия. Решая поставленные задачи, соответствующие целям исследования, автор определяет, что закреплённую в украинском законодательстве дефиницию понятия «коррупция» следует считать неоправданно ограниченной. Ввиду чего, подчёркивается необходимость приведения данного определения в соответствие с последними научными достижениями в теории коррупционной и антикоррупционной практики. In this article, the author pursues a goal to research the basic approaches to understanding the term “corruption” based on which he formulates the author's definition of the corresponding term. Achieving the goals of the research, the author determines that the definition of “corruption” enshrined in the Ukrainian legislation should be considered unreasonably narrowed. In view of this, this definition must be brought in line with the latest scientific achievements in the theory of corruption and anti-corruption practice. At the same time, in the course of current scientific literature analysis, the author determines that modern approaches to the corruption essence definition are based on traditional interpretation hypotheses about the term of corruption, namely within the framework of such approaches as: classical (corruption is the behavior of an official, which manifests itself in using his/her powers to achieve any private, individual or group goals); deep (this approach takes into account the actions of both the bribe taker and the bribe giver); broad (corruption is not only corrupt practices of officials, but also all kinds of misuse by these officials of public power for private gain). In view of the disadvantages of the existing approaches to understanding the corruption, the author formulates the appropriate combined approach, which takes into account the breadth of understanding relationship types in which payment can be interpreted as a bribe, on the one hand, and the depth of the structure of participants in these relations, on the other hand. Within the framework of the aforesaid approach, corruption is defined as deformation of the existing order of the “request-giving-taking” of public benefits or an attempt to violate this order, which is objectively conditioned by deviant actions that are carried out by a person: (1) having power and real influence in a society abusing this power (and influence) in exchange for items and/or services that satisfy his/her private interest (or interest of certain groups of people under his/her unauthorized protection); (2) desiring to receive benefit for him/herself or for third parties (including depriving a person of a benefit), and offering (including granting) to a person having power (and/or having relevant real influence in society) unauthorized corruption benefits in order to obtain an appropriate benefit; (3) who promotes active or passive acts of corrupt acts.
Basic Interpretative Hypotheses of the Concept of Corruption
Базовые интерпретационные гипотезы концепта коррупции
Keywords: bribery; bureaucracy; corruption; definition of corruption; бюрократия; взяточничество; коррупция; определение коррупции; бюрократія; визначення корупції; корупція; хабарництво; антикорупційний інструмент; правозастосовна практика; прозерпінаве потрясіння; дефініція корупції; дефиниция коррупции; корупційна злочинність